Pengaruh investasi asing langsung terhadap emisi CO2 dan produk domestik bruto di Malta - Ali Jufri; Bahri (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
Foreign direct investment (FDI) is a flow traditionally associated with the transfer of knowledge, technology, and management practices, and systems from the multinational company's home country to the host country. The relationship between FDI, CO2 emissions and economic growth has been explored from many aspects, as described in previous studies. The purpose of this study was to determine the effect of foreign direct investment on CO2 emissions and gross domestic product in Malta. This research using quantitative methods and uses regression analysis. The sampling method used is purposive sampling, with available data criteria. This research data is taken from the World Bank website for the period 1970-2018. The variables in this study are foreign direct investment (FDI) as independent variables, and CO2 emissions (CO2) and gross domestic product (GDP) as dependent variables. The results of data analysis show that foreign direct investment has a significant positive effect on CO2 emissions and gross domestic product in Malta. Suggestions for further research are to examine other variables related to foreign direct investment, such as exports and political aspects.